Pengaruh Persepsi Harga Dan Sikap Konsumen Terhadap Minat Beli Pada Produk Fast-Food Di Counter Hotfood Lulu Hypermarket Cakung - Dara Ramadanti; Hartono Hartono (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study aims to determine the effect of price perceptions and consumer attitudes on buying interest in fast-food products at the Lulu Hypermarket Hotfood Counter in Cakung. A quantitative research method was applied in this study. Questionnaires and literature review are utilized as data collection strategies. The study's participants are fast-food customers at the Lulu Hypermarket Cakung hot food court. In this study, non-probability sampling with a population sampling method was used as the sample strategy. There are 125 samples in all. Multiple linear regression analysis with SPSS version 23 was used to analyze the data. The results showed that price perception had an influence on purchase intention of 22.4%. Consumer Attitudes have an influence on Purchase Interest of 43.4%. Price Perceptions and Consumer Attitudes affect the Purchase Interest variable simultaneously with a value of 0.453 or 45.3% of which 54.7% is explained by other factors not included in this study.